Phenomenology involved in self-pressurized, natural circulation, low thermo-dynamic quality, nuclear reactors: The thermal–hydraulics of the CAREM-25 reactor - Marcel, Christian Pablo; Delmastro, Darío; Furci, H.f.; Masson, Viviana Patricia (Elsevier, 2013)
Fil: Marcel, Christian Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Area de Energía Nuclear. Instituto Balseiro; Argentina